The Potential of Water Hyacinth (Eichhornia crassipes) for the Phytoremediation of Curug Sigay Domestic Wastewater Using a Retention Pond - Polandos, Chersa Steffany; Rizki, Fajri Khoirul; Hendriantika, Ratu Dewi; Nurhaliza, Salma Setia; Sofiah, Siti; Surakusumah, Wahyu; Dewina, Restu Utari; Irawan, Afri (-, 2025)
The water hyacinth plant (Eichhornia crassipes) is often used for the phytoremediation process. This is because water hyacinth is a plant that is easy to find, besides that water hyacinth is able to grow in polluted waters and is able to produce biomass. This study aims to analyze changes in pH, TDS, temperature and DO levels in domestic wastewater at the Sigay waterfall which was treated with Eichhornia crassipes (water hyacinth) plants with the addition of palm fiber and gravel over a treatment period of 3, 6 and 9 days in retention ponds, as well to determine the optimum time for phytoremediation of Eichhornia crassipes in retention ponds. crassipes (Water hyacinth) during the experiment. The experimental reactor consisted of 3 treatments, namely water hyacinth fiber palm+gravel for 3 days (T-H3), 6 days (T-H6) and 9 days (T-H9) with reactor without treatment as the control. Each reactor is filled with 3L of leachate. The reactor is left in the open and exposed to sunlight. Data were processed using the ANOVA test. The results show a value of P= 0.027 for pH, P=0.026 for temperature, P=0.003 for TDS and 0.066 for the DO test with a value of α=0.05, which indicates that if P0.05 there is a significant difference between each treatment.